The active design of mixtures based on transition temperature of heat source for organic Rankine cycle. (February 2019) - Chen, Guibing; An, Qingsong; Zhao, Jun; Chang, Nini; Wang, Yongzhen; Yin, Hongmei; Hu, Likai; Gong, Yulie; Li, Xiaowei
Abstract: This paper presents a theoretical EEM (exergy efficiency model) to study active design of mixtures based on the transition temperature of heat source for subcritical ORC (organic Rankine cycle). 15 working fluids with critical temperature from 100 °C to 200°C are under evaluation. The exergy efficiency can be calculated quickly by the latent heat, specific heat at constant pressure and critical temperature based on the EEM. The maximal exergy efficiency will be obtained when the critical temperature of working fluid approaches to the heat source temperature. From the angle of reverse design, the ratios of mixtures can be calculated, whose exergy efficiency is higher than pure working fluids. Under the transition temperature, the exergy efficiency exists the maximum value with the OET. The increase of the OET is monotonous but not linear as the heat source temperature goes up.